2014
DOI: 10.5209/rev_hics.2013.v18.44225
|View full text |Cite
|
Sign up to set email alerts
|

Uso de redes sociales como elemento de interacción y construcción de contenidos en el aula: cultura participativa a través de Facebook.

Abstract: ResumenDe cara al S.XXI, es necesario innovar dentro de las aulas con recursos utilizados por los nativos digitales. La innovación debe presentarse como elemento motivador, por lo que implementarla es un gran reto. Las redes sociales han permitido que estudiantes y docentes interactúen de una manera más natural al usar lenguajes que utilizan para actividades fuera del aula. En esta Investigación se pretende conocer si la estrategia de implementación de Facebook en las clases, es aceptada por los estudiantes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
5
0
4
Order By: Relevance
“…Applications such as Facebook, Twitter and MySpace, amongst others, are specifically identified as emerging techniques applicable to teaching and learning. They can meet various needs of student diversity, flexibility, and ubiquity, and facilitate collaboration and communication between instructors and students, also causing the latter to be responsible for their learning (Alvarez-Flores and Nuñez, 2013). Web 2.0 tools are so popular in education that it is merely sufficient to inspect the list of the top 200 Tools for Learning to realize how they dominate the list (Top 200 tools for learning, 2017).…”
Section: Theoretical Framework 21 the Web 20 Applicationsmentioning
confidence: 99%
“…Applications such as Facebook, Twitter and MySpace, amongst others, are specifically identified as emerging techniques applicable to teaching and learning. They can meet various needs of student diversity, flexibility, and ubiquity, and facilitate collaboration and communication between instructors and students, also causing the latter to be responsible for their learning (Alvarez-Flores and Nuñez, 2013). Web 2.0 tools are so popular in education that it is merely sufficient to inspect the list of the top 200 Tools for Learning to realize how they dominate the list (Top 200 tools for learning, 2017).…”
Section: Theoretical Framework 21 the Web 20 Applicationsmentioning
confidence: 99%
“…At the same time, there are some studies that have framed the scholar interactions in terms of communication as a more complex and wider process than mere interactivity (Alvarez-Flores & Gómez, 2013;Hershkovizt & Forkosh-Baruch, 2017;Leite, Hoji, & Junior, 2018;Seifert, 2016;Túñez & Sixto, 2012). The review carried out by Froment, García, and Bohórquez (2017) on the impact of SNSs on teacher-student communication is remarkable.…”
Section: Teacher-student Interaction and Communicationmentioning
confidence: 99%
“…This may suggest some limitationswhen leading students to develop their total activity exclusively across digital spaces. On the one hand, some limitations are related to the promotion of learners' passive attitudes towards participation, lower commitment of teachers when students use digital environments, or the lack of physical teacher-student' interaction (Alvarez-Flores & Gómez, 2013;Ling, 2014;Martínez, 2014;Norman et al, 2015;Rama & Chiecher, 2012;Túñez & Sixto, 2012). On the other hand, other studies have found a relationship between the frequency in the use of SNSs and academic achievement, so that the latter increases when the student displays a moderate use of SNSs (Abu-Shanab & Al-Tarawneh, 2015;Al-Yafi, El-Masri, & Tsai, 2018;Paul, Baker, & Cochran, 2012) and avoids passive or addictive uses (Arquero & Romero-Frías, 2013;Buck, 2012;Gafni & Deri, 2012;Huang, 2018).…”
Section: Teacher-student Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the professor must strategically plan the objectives of this network, join them with the subjects' objectives and motivate students (Álvarez-Flores and Núñez Gómez, 2013). As critical perspective, it has been mentioned that the university is evolving in an excessively slow manner compared to the professional practice of journalism and it was specified that technological alphabetization is not condition enough for the narrative alphabetization needed in the professional practice on media.…”
Section: Main Conclusion Of Analyzed Articlesmentioning
confidence: 99%